PREDIKSI TINGKAT KEBANGKRUTAN PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR Di BURSA EFEK INDONESIA TAHUN 2014-2015: (Dengan Metode Z-Score Altman Dan Z-Score Foster) - Erwita Dewi (Jurnal Sains Sosio Humaniora, 2017)
This study aims to determine the financial statements prior to the bankruptcy can be used to predict the rate of bankruptcy with Altman Model and Foster on coal mining company listed on the Indonesia Stock Exchange. Model classification Altman Z score Z score> 2.90 is classified as a healthy company, while the company has a Z score <1.20 were classified as potentially bankrupt company. Furthermore, scores between 1.20 to 2.90 is classified as a company in the gray area or the gray area. While the Model Z score Foster use the "Cut-off Point" Z = 0.640, so companies that have Z < 0.640 belongs to a group of companies that go bankrupt, while if Z > 0.640 included in the group of companies that are not bankrupt. After that tested the difference between the predicted results using independent samples t test. The results of the analysis of financial ratios and Foster Altman model proved capable of predicting corporate bankruptcies coal mining sector in Indonesia Stock Exchange in 2014-2015. Results Zscore Altman bankruptcy prediction for the year 2014-2015 shows an increase in predictive companies entering bankrupt category. In 2014 by 22% (there are four companies that PT.BUMI Resources Tbk, PT.Darma Henwa Tbk, PT.Delta Dunia Makmur Tbk and PT.Perdana Karya Perkasa Tbk), and in 2015 by 44% (there are eight companies, namely PT. Adaro Energy Tbk, PT.Atlas Resources Tbk, PT. Bumi Resources Tbk, PT. Darma Henwa Tbk, PT. Delta Dunia Makmur Tbk, PT.Perdana Karya Perkasa Tbk, PT.Petrosea and PT. Golden Eagle Energy Tbk). Foster Zscore bankruptcy prediction results for the year 2014-2015 shows that there is consistency predictive companies entering bankrupt category. Year 2014-2015 by 28% (there are five companies that PT.Atlas Resources Tbk, PT.Baramulti Sukses sarana Tbk, PT. Bayan Resources Tbk, PT. Darma Henwa Tbk and PT. Perdana Karya Perkasa Tbk). Both models are Zscore Altman bankruptcy prediction and Zscore Foster in this study proved to be no different in corporate bankruptcy prediction results were proved by analysis of independent sample t test.